The Economic Case for Devoting Public Resources to Health - David E. Bloom; Günther Fink (Institute for the Study of Labor (IZA), 2013)
The world has enjoyed huge improvements in population health during the last half century. But major health problems persist, particularly in tropical countries, which are still struggling with infectious diseases while increasingly having to deal with noncommunicable diseases. Several classic arguments for public spending on health have buttressed governments' efforts to improve health. These efforts have now been further spurred by new economic arguments that better population health may promote economic well-being via beneficial changes in labor productivity, education, and investment, and through demographic change. The economic consequences of improved health can be large, but realizing them depends on the policies adopted in myriad other arenas.
Keywords: I15; I14; I18; H51; 330; investment in health; labor productivity; education; demographic change; health gaps; Gesundheitspolitik; Gesundheitskosten; Wirkungsanalyse; Gesundheit; Makroökonomischer Einfluss; Welt; Regenwald